Style of Imam Al-Khattabi in Ma’limus Sunan; an Exegesis of Sunan Abi Dawood - Dr. Hafiz Qudrat Ullah; Dr. Muhammad Usman Khalid (jihat-ul-islam, 2022)
Imam Al-Khattabi has been a prolific prose writer, an outstanding Muhaddith, an eminent expert of jurisprudence, an authentic interpreter, an accomplished writer, and a poet of Arabic language. His writings based on knowledge of Hadith, jurisprudence, and rectification of Arabic vocabulary are considered an authority. Imam Khattabi narrated Ahadits of Sunan Abi Dawood via medium of Ibn e Dasa. Imam Al-Khattabi has the privilege of being one of early interpreters of Sahi Ul Bukhari and Sunan Abi Dawood. His successors have been continuously benefited from his interpretations. He is well-known for his interpretations of Elam Ul Hadith and Ma’limus Sunan.His manuscripts are a beautiful blend of brevity, simplicity, and commonsense. He utilized his expertise in both the Arabic language and literature at the service of Prophet of Islam. He offered his services in two ways. Firstly, he explained, interpreted and made easy for people to comprehend difficult words of Arabic language in his book Ghareeb Ul Hadith, which is a seminal and authentic work in this field. He examined around 1230 Ahadits and the sayings of the companions of the prophet and elucidated them. Secondly, there were some errors in the content or words of Ahadiths and chain of narration either misspelled or mispronounced. He not only identified the discrepancies but also rectified them. He deduced matters related to jurisprudence from the interpretation of Ahadiths. He also brought agreement to semingly two contradictory ahadiths, allowing both to be acted upon. During the rigorous process of explaining Ahadits, he separated weak narrations from the stronger ones and criticized the unauthentic reporters.